2009
DOI: 10.1007/s11101-009-9136-6
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics analysis of the Lolium perenne–Neotyphodium lolii symbiosis: more than just alkaloids?

Abstract: Above ground plant parts of Lolium perenne often harbour endophytic Neotyphodium lolii fungi. These occur both naturally and commercially, as variant strains are introduced to modify the grass metabolic profile. They reside in the apoplastic spaces and rarely cause visible symptoms of infection. The vast majority of literature has focussed on the biosynthesis, accumulation, and ecological relevance of a limited number of alkaloids produced by N. lolii which have been shown to negatively affect insect pests and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 102 publications
4
47
1
Order By: Relevance
“…In addition to the presence of fungal produced alkaloids, the concentrations of numerous other metabolites are altered in endophyte-infected plants. Nitrogenous compounds, such as total N, nitrate, total proteins, and free amino acids were reduced in endophyte-infected plants, whereas carbohydrates were increased [10], [11]. In some grass-endophyte symbiotic systems the endophyte was found to utilize plant produced asparagine and glutamine as precursors in the synthesis of lolines, and the levels of lolines synthesized by the endophyte were regulated by levels of the amino acids provided by the plant [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the presence of fungal produced alkaloids, the concentrations of numerous other metabolites are altered in endophyte-infected plants. Nitrogenous compounds, such as total N, nitrate, total proteins, and free amino acids were reduced in endophyte-infected plants, whereas carbohydrates were increased [10], [11]. In some grass-endophyte symbiotic systems the endophyte was found to utilize plant produced asparagine and glutamine as precursors in the synthesis of lolines, and the levels of lolines synthesized by the endophyte were regulated by levels of the amino acids provided by the plant [12].…”
Section: Introductionmentioning
confidence: 99%
“…The potential precursors for loline biosynthesis (asparagine, homoserine and proline) were also substantially reduced in N. uncinatum and N. siegelii infected meadow fescue, indicating lolines acting as a possible sink for these amino acids (Zhang et al, 2009). But note that lolines can accumulate to unusually high concentrations in meadow fescue, while alkaloid concentrations in other associations are much lower, making it unlikely that amino acid reductions are directly linked to alkaloid biosynthesis (Rasmussen et al, 2009). Even though alkaloids are usually perceived as the major factor affecting insect herbivores, a linear regression analysis of metabolic profiles with insect abundances indicated that a particular 'type' of metabolic composition, rather than any one individual compound, might be important for specific insect responses (Rasmussen et al, 2008b).…”
Section: Neotyphodium -Grass Associationsmentioning
confidence: 98%
“…A strong reduction in free nitrate, the amino acids asparagine and proline, and proteins, and a concomitant increase in soluble carbohydrates (glucose, fructose, sucrose, fructans), organic acids (quinate, shikimate) and phenylpropanoids (chlorogenic acid) indicate an increase in C/N ratios and defence compounds (Rasmussen et al, 2008a). Mechanisms for these changes in metabolic profiles remain elusive, but they could be related to effects of endophytes on nitrate uptake/ transport/ reduction or photosynthetic activity (Rasmussen et al, 2009). The potential precursors for loline biosynthesis (asparagine, homoserine and proline) were also substantially reduced in N. uncinatum and N. siegelii infected meadow fescue, indicating lolines acting as a possible sink for these amino acids (Zhang et al, 2009).…”
Section: Neotyphodium -Grass Associationsmentioning
confidence: 99%
“…High-profile applications include identification of diagnostic biomarkers for cancer, mapping of genetic loci that are associated with metabolite level variation in human blood samples, and deciphering of complex metabolite-based interactions between species. [15][16][17] Similar approaches have also been used in microbial cell-factory host organisms such as Saccharomyces cerevisiae to map the effects of genetic changes on metabolite concentrations, allowing the top-down reconstruction of previously poorly understood metabolic pathways. 18 In general, metabolomics has the potential to become one of the standard methods for mapping genotype-to-phenotype relationships in biological systems ranging from microbes to plants and humans.…”
Section: Metabolomics and Metabolite Profilingmentioning
confidence: 99%
“…This type of application is conceptually similar to the use of metabolomics to understand the genetic underpinnings of metabolic traits that rely on using large metabolomic and genomic datasets to perform systematic mapping of genotypemetabolic phenotype relationships. [15][16][17] With the significantly decreased costs of genome resequencing in recent years, metabolomics and sequencing-based methods can be combined in the cell-factory development process to provide rapid and low-cost characterization of engineered strains derived either by rational or combinatorial strategies. Sequencing allows genotype determination of strains created by random or semi-random approaches such as adaptive laboratory evolution or multiplex automated genome engineering.…”
Section: Metabolomicsmentioning
confidence: 99%